Struktur Floristik Hutan di Kawasan Lindung Sempadan Sungai dalam Areal Hutan Tanaman Industri - Qomar, Nurul; Bahdarsyah, Bahdarsyah; Nugroho, P Agung; Rohaini, Rahmi A; Muhammad, Ahmad (Jurnal Natur Indonesia, 2007)
This study was carried out in riparian conservation forests within a monospecific pulpwood estate in Sorek,Pelalawan District, Riau. The remaining natural forests comprised lowland rainforest (at Sei Buluh and Tolamriversides), mixed swamp forest (at Telayap riverside), and pole forest (at Rangsang riverside). The objective of thecurrent study was to describe the floristic structure of each forest type at the conservation areas in concern.Fifteen transects (width of 20 m) were established at all sites with a total length of 8.080 m. Quadrates plots of 20x 20 m were established with continue on these transect for tree sampling (dbh > 20 cm) and smaller quadrates(10 x 10 m) were nested on each one of the former for pole sampling (dbh 10 – 20 cm). The parameters used in thisstudy were Importance Value (IV), species richness (Margalef Index = R1 and Menhinick Index = R2), and Diversity Index (Shannon = H’ and Simpson = D). Results showed that in tree stratum, the largest basal area (11.25 m2ha-1) and the highest diversity was found at Telayap’s riverside (H’ = 3.70 and D = 0.98). Species richness was most profound at Tolam riverside (R1 = 10.43 and R2 = 2.83). Rangsang’s riverside possessed the highest tree density (105 individuals ha-1) but with the smallest dbh (26.5 cm). This forest was a peat-swamp forest predominating by bintangur (Calophyllum pulcherimum). At the pole stratum, the largest basal area (7.00 m2ha-1) and the highest diversity was found at Tolam riverside (H’ = 3.39 and D = 0.96). Species richness was most profound at Telayap’s riverside (R1 = 8.89 and R2 = 2.64). The highest pole density (380 individuals ha-1) was observed at Sei Buluh’s riverside, in which mempening (Quercus lucida Roxb.) was predominating. Acacia mangium was establishing very well at all sites, indicating its adaptability and potentially invasive feature.